Activation and Enhancement of the Performance of Iraqi Ca-Bentonite for Using as Drilling Fluid in Iraqi Oil Fields - Ibrahim, Ahmed Sattar; Al-Bidry, Mayssaa Ali (Iraqi Journal of Science, 2020)
In this study, Iraqi bentonite taken from Trefawi area/ Al-Anbar region province/ Iraq, was activated to enhance its rheological and filtration properties and increase its quality by decreasing the non-clay minerals (impurities), in order to be used in Iraqi oil companies instead of commercial bentonite. Bentonite was characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF) and particle size distribution (PSD) before and after activation to show the effects on its mineral and chemical properties. The rheological properties of bentonite were enhanced by using different weights (0.4, 0.5, 0.6, 0.7 and 0.8 gm) of sodium carbonate (Na₂CO₃), whereas the filtration properties were enhanced by using different weights (0.5, 1, 1.5 gm) of high viscous-carboxy methyl cellulose (CMC-HV) and different weights (0.5, 1, 2 gm) of low viscous-carboxy methyl cellulose (CMC-LV). The results showed that the rheological properties of Iraqi bentonite were enhanced and met the specifications of the American Petroleum Institute (API) when 0.7 gm of Na₂CO₃ was added. The filtration properties were also enhanced and satisfied API specification when 0.5 gm of CMC-HV and 2 gm of CMC-LV were added. Therefore, Iraqi bentonite has the potential to be used as drilling fluid in oil fields.